Policy Development in the Tripartite Alliance, 2007-2012: An application of the Multiple Streams Framework - Cupido, Simone (Department of Political Studies, 2022)
The tripartite alliance is an unusual structure of governance which consolidates the rule of the African National Congress (ANC) as a dominant party through three parties each with a unique ideological trajectory and constituency base. The structure is a unique space for policy formulation and agenda setting and often finds itself in conflict about policy approaches and directives. In 2012 the National Development Plan (NDP) came into fruition and the period prior to its production saw policy consensus on developmental policy approaches within the Tripartite Alliance as a structure. Using this instance of policy making within the Tripartite Alliance this thesis asks: How does policy happen with in the Tripartite Alliance. To answer this question, the public policy scholarship framework known as the Multiple Streams Framework as founded by John Kingdon, breaks policy processes into three distinct themes, analysing exactly how policy occurs in the structure. This analysis will therefore test the theory of the Multiple Streams Framework on the case study of development policy making within the tripartite alliance between 2007 and 2012, discerning how useful it is in answering how policy happens within the structure.